Digital and Collaborative Marketing Strategy for Palutungan Camping Ground Based Tourism Development - Enda Sukenda; Azhar Affandi; Yudhi Koesworodjati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Palutungan Camping Ground, located within the Mount Ciremai National Park in Kuningan Regency, West Java, faces a 19.68% decline in tourist visits in 2023, highlighting the need for effective marketing strategies to enhance its appeal as a nature-based tourism destination. This study aims to analyze current marketing strategies, evaluate visitor performance, identify operational challenges, and propose an integrated tourism area strategy to increase tourist visits. Employing a descriptive qualitative approach with a single case study design, data were collected through semi-structured interviews with stakeholders, including park officials and community leaders, alongside field observations and secondary sources. The findings reveal that Palutungan relies on natural attractions like the Curug Putri waterfall but struggles with limited digital marketing and infrastructure deficiencies. A SWOT analysis identifies strengths in natural assets and opportunities in zoning systems, while weaknesses include waste management and limited capital. Digital marketing enhances destination visibility, supporting proposed strategies like social media campaigns and inclusive zoning. The study concludes that an integrated marketing strategy, incorporating digital promotion, stakeholder collaboration, and infrastructure improvements, can reverse the decline and ensure sustainable tourism growth at Palutungan.